Uma experiência didática de corrosão usando colorimetria visual - Bidetti, Bárbara Bidoia [UNESP]; Balthazar, Priscila Aoki [UNESP]; Vaz, Ednilson Luiz Silva [UNESP]; Codaro, Eduardo Norberto [UNESP]; Acciari, Heloisa Andréa [UNESP] (Sociedade Brasileira de Química, 2012)
In this paper, a simple and rapid method of evaluating galvanized steel sheet corrosion in a CuSO4 solution, as an experimentation proposal for corrosion teaching. Galvanized steel corrosion is present in tanks and tubing by leading of natural or industrial waters which contain soluble copper compounds. This was the rationale for choosing the Cu2+ ions solution as an oxidizing agent. The method principle is based on visual colorimetry because the used oxidant has an intense blue color. Thus, a change in its concentration as a result of the corrosive process can be followed by a color intensity change in the solution thereby allowing evaluation of the corrosion rate.
A teaching experiment of corrosion using visual colorimetry
Keywords: chemistry education; corrosion; social interaction